DIFFERENTIAL APPROACH TO URINARY SYNDROME VERIFICATION IN MEDICOPROPHYLACTIC FACILITIES IN CHILDREN WITH URINARY TRACT INFECTIONS - E.M. Pleshkova; A.A. Yailenko ("Paediatrician" Publishers LLC, 2011)
Urinary syndrome is an invariable and often the only manifestation of renal and urinary tract injury. Modern laboratory diagnostics prioritize prompt tests such as «dry chemistry» urine analysis using deep-stick tests. Study objective: to evaluate diagnostic accuracy of deep-stick tests in urinary syndrome verification in pediatric urinary tract infections (UTI). Methods: examination of a urinary sample using standard methods and prompt analysis with urine biochemical composition analyser among 66 children aging from 2 months to 16 years. From this group: 28 children had UTI and 38 other somatic diseases. Results: it has been shown that nitrite test-sticks have low diagnostic sensitivity - 69%, high prognostic value of a positive result (90%) and high specificity (94%). Diagnostic sensitivity of leucocytic esterase is 73%, its' prognostic value of a positive result - 92% and diagnostic specificity - 94%. Erythrocyteuria test had diagnostic sensitivity of 80% and specificity of 95%. Protein test had diagnostic sensitivity of 61% and prognostic value of 64% and 81% specificity. Conclusion: deep-stick test implementation with regard to specifications of this method will allow a more differential approach to it's use in labs of medicoprophylactic facilities, also reduce the amount of time required for lab urine examinations, as well as to increase reliability of diagnostic information. Key words: children, urinary tract infections, stick-tests, «dry chemistry», diagnostic accuracy, method, urinalysis. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 89-95)